Application of enhanced recovery after surgery in patients undergoing radical cystectomy - Wei, Chunxiao (J Int Med Res, 2018)
OBJECTIVE: This study was performed to evaluate the application of enhanced recovery after surgery (ERAS) in patients undergoing radical cystectomy (RC). METHODS: The clinical data of 192 patients who underwent RC were collected in this retrospective cohort study. Among them, 91 patients who underwent ERAS were allocated to the ERAS group, and the remaining 101 patients who underwent traditional postoperative care procedures were allocated to the non-ERAS group. Perioperative indexes in the two groups were compared. The ERAS components included rehabilitation exercise, carbohydrate fluid loading, cessation of nasogastric tubes, omission of oral bowel preparation, regional local anesthesia, body-warming procedures, reduced drainage use, and early postoperative drinking and eating. RESULTS: The times from RC to first water intake, first ambulation, first anal exhaust, first defecation, and pelvic drainage tube removal were significantly shorter and the hospitalization costs were significantly lower in the ERAS than non-ERAS group. The intraoperative blood loss volume, blood transfusion rate, readmission rate, and incidence of postoperative complications were also significantly lower in the ERAS than non-ERAS group. CONCLUSION: ERAS may effectively accelerate patient rehabilitation and reduce the length of stay, incidence of postoperative complications, readmission rates, and hospitalization costs for patients undergoing RC.